2018
DOI: 10.1242/jeb.175281
|View full text |Cite
|
Sign up to set email alerts
|

Short term colour vision plasticity on the reef: Changes in opsin expression under varying light conditions differ between ecologically distinct reef fish species

Abstract: Vision mediates important behavioural tasks such as mate choice, escape from predators and foraging. In fish, photoreceptors are generally tuned to specific visual tasks and/or to their light environment, according to depth or water colour to ensure optimal performance. Evolutionary mechanisms acting on genes encoding opsin, the protein component of the photopigment, can influence the spectral sensitivity of photoreceptors. Opsin genes are known to respond to environmental conditions on a number of time scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 108 publications
6
43
0
Order By: Relevance
“…() found that placing pomacentrids and apogonids into tanks with different red, green or blue lighting results in plastic adaptations in opsin gene expression. Interestingly, while pomacentrids mostly adjusted the expression of their single cone opsins ( SWS1 and SWS2 ), the apogonids showed the greatest plasticity in their double cone genes ( RH2 and LWS ) (Luehrmann et al ., ) this making some sense as apogonids are primarily nocturnal and may need greater plasticity in their more sensitive double cones. Several reef‐fishes are furthermore known to exist over substantial depth ranges where ambient illumination may differ greatly.…”
Section: Reef Fishes Colour Visionmentioning
confidence: 99%
See 3 more Smart Citations
“…() found that placing pomacentrids and apogonids into tanks with different red, green or blue lighting results in plastic adaptations in opsin gene expression. Interestingly, while pomacentrids mostly adjusted the expression of their single cone opsins ( SWS1 and SWS2 ), the apogonids showed the greatest plasticity in their double cone genes ( RH2 and LWS ) (Luehrmann et al ., ) this making some sense as apogonids are primarily nocturnal and may need greater plasticity in their more sensitive double cones. Several reef‐fishes are furthermore known to exist over substantial depth ranges where ambient illumination may differ greatly.…”
Section: Reef Fishes Colour Visionmentioning
confidence: 99%
“…Also, marine fishes such as the yellowfin tuna Thunnus albacares (Bonnaterre 1788) (Loew et al ., ) and starry flounder, Platichthys stellatus (Pallas 1787) (Savelli et al ., ) co‐express multiple opsin pigments during development, but the functionality of this remains elusive. Co‐expression of visual pigments seems a prominent feature of many reef fishes also with detailed studies in pseudochromids and P. leopardus (Cortesi et al ., 2016), opmacentrids (Luehrmann et al ., ), and squirrelfishes (Holocentrinae; F. de Busserolles, N.J. Marshall, & S.P. Collin, unpublished data).…”
Section: Reef Fishes Colour Visionmentioning
confidence: 99%
See 2 more Smart Citations
“…The particular methods used to normalize opsin expression are important because there is incredible variation in opsin expression across animals depending on the time of day (Halstenberg et al, ; Johnson et al, ; Korenbrot & Fernald, ; Li et al, ; Pierce et al, ; von Schantz et al, ), genetic variation and species differences (Fuller, Carleton, Fadool, Spady, & Travis, ; O’Quin et al, ), developmental stage (Carleton et al, ; Cheng & Flamarique, ; Roberts, Srinivas, Forrest, Escobar, & Reh, ), and plastic response to environmental changes (Everett, Tong, Briscoe, & Monteiro, ; Fuller & Claricoates, ; Hofmann, O’Quin, Smith, & Carleton, ; Luehrmann et al, ; Stieb, Carleton, Cortesi, Marshall, & Salzburger, ; Valen, Karlsen, & Helvik, ; Veen, Brock, Rennison, & Bolnick, ). There have been five commonly used methods, each with their own merits and drawbacks, to normalize opsin expression for questions of visual ecology and evolution: (a) relative to housekeeping gene expression, (b) relative to total RNA concentration, (c) relative to expression of the cone‐specific alpha subunit of transducin ( GNAT2) , (d) proportion of total pool of opsin expression and (e) relative to pool of opsin expression from the same cone type.…”
Section: Introductionmentioning
confidence: 99%